(untitled) (Proceedings International Conference on Fisheries and Aquaculture, 2021)
Due to food safety and public health concerns, much interest has been placed on antibacterials derived from natural products for use in aquaculture. Kaempferia parviflora and Curcuma longa, herbs that can be found in Thailand, have been shown to possess antibacterial properties. The biological activities of these herbs, however, was found to be dependent on age. Here, ethanol extracts of K. parviflora and C. longa harvested at different periods were evaluated for their antibacterial activity against 5 strains of bacteria, pathogenic to aquatic animals, using disc diffusion method. Our results revealed that K. parviflora ethanol extracts at 9 and 10 months after planting showed antibacterial activity only against Vibrio harveyi and V. parahaemolyticus, while C. longa ethanol extracts at 7, 8, 9 and 10 months after planting exhibited antibacterial activity against V. harveyi, V. parahaemolyticus, Edwardsiella tarda and Streptococcus agalactiae. Both K. parviflora and C. longa ethanol extracts show no inhibitory effect on Escherichia coli. Comparison of the zone of inhibitions suggest that the suitable time to harvest K. parviflora and C. longa for ethanol extraction was 9 and 10 months after planting, respectively. The minimum inhibitory concentrations of K. parviflora and C. longa ethanol extracts during the above mentioned periods ranged from 12.50 to 50.00 and 3.12 to 50.00 mg/ml, respectively. In conclusion, both herbs have exhibited antibacterial activity against V. harveyi, V. parahaemolyticus, E. tarda and S. agalactiae. C. longa ethanol extract, specifically, showed better inhibitory properties and can thus be potentially useful for aquaculture in the treatment of bacterial infections